2016
DOI: 10.3390/rs8120993
|View full text |Cite
|
Sign up to set email alerts
|

Inversion of Land Surface Temperature (LST) Using Terra ASTER Data: A Comparison of Three Algorithms

Abstract: Land Surface Temperature (LST) is an important measurement in studies related to the Earth surface's processes. The Advanced Space-borne Thermal Emission and Reflection Radiometer (ASTER) instrument onboard the Terra spacecraft is the currently available Thermal Infrared (TIR) imaging sensor with the highest spatial resolution. This study involves the comparison of LSTs inverted from the sensor using the Split Window Algorithm (SWA), the Single Channel Algorithm (SCA) and the Planck function. This study has us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…In previous studies on SURFRAD stations [53,56,65], the broadband emissivity was computed as reported in [104,105] by regression from narrowband emissivity of MODIS thermal bands, which are available through the MODIS monthly emissivity data set. The results in [104,105] proved that the longwave broadband emissivity for the SURFRAD sites could be considered 0.97, as also assumed in [64] and [53].…”
Section: Lst Computation Using Ground-based Surfrad Datasupporting
confidence: 57%
See 1 more Smart Citation
“…In previous studies on SURFRAD stations [53,56,65], the broadband emissivity was computed as reported in [104,105] by regression from narrowband emissivity of MODIS thermal bands, which are available through the MODIS monthly emissivity data set. The results in [104,105] proved that the longwave broadband emissivity for the SURFRAD sites could be considered 0.97, as also assumed in [64] and [53].…”
Section: Lst Computation Using Ground-based Surfrad Datasupporting
confidence: 57%
“…Besides, ancillary observations include direct and diffuse solar radiation, ultraviolet-B radiation, and meteorological parameters. Since SURFRAD stations provide unique in-situ LST information over rural sites, many researchers have used these data to validate satellite-based LST retrievals [15,46,52,53,56,[64][65][66][67]. In this study, five SURFRAD stations were considered as ground-based stations, and Table 1 reports information regarding the SURFRAD experimental sites.…”
Section: Surfrad Data and Validation Sitesmentioning
confidence: 99%
“…The calculation of the SUHI was performed in six steps ( Figure 2), as follows: (i) was to convert the digital numbers into radiance; (ii) to calculate brightness temperature; (iii) to calculate the NDVI (Normalized Difference Vegetation Index); (iv) to estimate the surface emissivity using the values obtained by the NDVI; (v) after estimating emissivity, to determine the corrected surface temperature, which was later transformed into SUHI in the sixth step, as suggested by Ndossi and Avdan [47,48].…”
Section: Methodsmentioning
confidence: 99%
“…[46]. LANDSAT satellite sensors have been monitoring the Earth for over four decades, providing data continuity during this period [47,48]. The first series of this satellite was launched in 1972, named LANDSAT 1.…”
Section: Urban Sci 2020 4 X For Peer Review 3 Of 19mentioning
confidence: 99%
“…Specifically, the satellite has 15 visible and NIR bands (0.402-0.965 µm), four shortwave infrared bands (1.02/1.23-2.155 µm), two medium-wave infrared bands (3.71-4.1275 µm), one water vapor band (6.95-7.45 µm) and three longwave infrared bands (8.4-12.5 µm). In terms of product applications, channels 1-7 are mainly used for land and cloud boundaries; channels 8-15 are used for ocean color, plankton and biogeochemical remote sensing; channels 16,17,18,22, and 23 are used for atmospheric water vapor remote sensing; channel 19 is a cloud band; and channels 20, 21, 24, and 25 are used for land, water, and cloud temperature sensing. Table 1 shows the continuity and evolution of the MERSI to MERSI-2 bands and the comparison of MERSI-2 with MODIS, MERSI, and VIIRS.…”
Section: Data Introductionmentioning
confidence: 99%